2007
DOI: 10.1242/dev.02729
|View full text |Cite
|
Sign up to set email alerts
|

Oskar controls morphology of polar granules and nuclear bodies inDrosophila

Abstract: Germ cell formation in Drosophila relies on polar granules, which are large ribonucleoprotein complexes found at the posterior end of the embryo. The granules undergo characteristic changes in morphology during development, including the assembly of multiple spherical bodies from smaller precursors. Several polar granule components, both protein and RNA, have been identified. One of these, the protein Oskar, acts to initiate granule formation during oogenesis and to recruit other granule components. To investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 25 publications
7
22
0
Order By: Relevance
“…The former two resembled nuclear germ granules described in PGCs (Fig. 2B, Ci)(Jones and Macdonald, 2007; Mahowald, 1962; Mahowald et al, 1976), while the latter were observed only in S2R+cells. Importantly, the formation of these granules depended on Short Osk and not on the mCherry fluorophore or the orientation of the fluorescent tag, as N- and C-terminally-tagged Short Osk formed the same granules (Fig.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The former two resembled nuclear germ granules described in PGCs (Fig. 2B, Ci)(Jones and Macdonald, 2007; Mahowald, 1962; Mahowald et al, 1976), while the latter were observed only in S2R+cells. Importantly, the formation of these granules depended on Short Osk and not on the mCherry fluorophore or the orientation of the fluorescent tag, as N- and C-terminally-tagged Short Osk formed the same granules (Fig.…”
Section: Resultssupporting
confidence: 73%
“…As with cytoplasmic germ granules, we could not detected fusion of nuclear germ granules. Nuclear granules did not result from over-expression of Osk:GFP or Vasa:KuOr since they have been previously observed in wild-type flies using EM and immunofluorescence(Jones and Macdonald, 2007; Mahowald, 1962; Mahowald et al, 1976). Because nuclear granules formed only in PGCs (Fig.…”
Section: Resultssupporting
confidence: 58%
“…It has been shown that even among species in the Drosophila genus, germ granule morphology and size is variable [25]. Later studies showed that the differences were due to species-specific properties of Osk proteins [26]. Changes in Osk protein can also lead more drastic changes in the protein’s function.…”
Section: Evolution Of Oskar and The Origins Of Maternal Provision Inmentioning
confidence: 99%
“…Osk is the pivotal organizer which anchors other granule components and controls granule morphology [9], [28]. Based mainly on the normal localization of Vas in tud embryos and the defective localization of Tud in vas embryos [18], [19], a pathway for pole plasm assembly has been proposed in which tud acts downstream of vas (see, for example, [29]).…”
Section: Discussionmentioning
confidence: 99%